PELATIHAN MANAJEMEN DAN AKUNTANSI UNTUK BADAN USAHA MILIK DESA DI PULAU MAKIAN HALMAHERA SELATAN - Grace Persulessy; Evi Maria (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service activity is to provide knowledge and skills about management and accounting for Village-Owned Enterprises (BUMDes). This activity was attended by the management of BUMDes in eight villages, Makian Island, South Halmahera with a total of 40 participants. The methods used are lectures, group practices, and evaluations. The result of this activity is that BUMDes management can make BUMDes business plans using canvas models and can carry out simple accounting records, including cash records, budget realization reports, and income statements.Keywords: management, accounting, Village-Owned Enterprises.